Mediator-lipidomics: databases and search algorithms for PUFA-derived mediators - Yan Lu; Song Hong; Eric Tjonahen; Charles N. Serhan (Journal of Lipid Research, 2005)
Lipid mediators (LMs) derived from PUFAs play important roles in health and disease. Databases and search algorithms are crucial, but currently unavailable, for accurate and prompt analysis of LMs via liquid chromatography-ultraviolet-tandem mass spectrometry (LC-UV-MS/MS). A novel algorithm and databases, cognoscitive-contrast-angle algorithm and databases (COCAD), were developed for the identification of LMs based on the integration of standard MS/MS spectra with chromatograms and UV spectra. Segment naming and empirical fragmentation rules were introduced to determine MS/MS ion identities, along with ion intensities used by COCAD in matching the unknown to those of authentic standards. The structures of potential LMs without synthetic and/or authentic products as standards were identified by developing theoretical databases and algorithms based on virtual LC-UV-MS/MS spectra and chromatograms. The performance of these databases and algorithms was tested by identifying LMs in murine tissues.These results indicate that COCAD has many advantages for profiling and identification of LMs compared with the conventional dot-product algorithm.